Diagnosis and management of pulmonary hypertension in infants with bronchopulmonary dysplasia. Issue 4 (August 2022) - Levy, Philip T.; Levin, Jonathan; Leeman, Kristen T.; Mullen, Mary P.; Hansmann, Georg; Kourembanas, Stella
Abstract: Chronic pulmonary hypertension of infancy (cPHi) is a heterogeneous disease process that contributes to morbidity and mortality in preterm infants. cPHi is most commonly associated with chronic lung disease of prematurity and represents a unique phenotype of bronchopulmonary dysplasia. It is characterized by persistently elevated or newly rising pulmonary vascular resistance and pulmonary artery pressure beyond the first weeks of age. The high-pressure afterload on the right ventricle may or may not be tolerated, depending upon additional cardiovascular shunting and co-morbidities. A comprehensive clinical evaluation combined with advanced hemodynamic assessment by echocardiography and other cardiac imaging modalities help decipher the etiopathologies of disease, identify cardiopulmonary compromise earlier and guide individualized therapeutic intervention tailored by the phenotype. This review summarizes the underlying etiologies, risk factors for development, hemodynamic assessment, management, and follow-up of cPHi in preterm infants. We offer an algorithm for early detection of cPHi and outline research priorities.